Development and application of the direct mycobacterial growth inhibition assay: a systematic review - Painter, Hannah; Harriss, Eli; Fletcher, Helen A.; McShane, Helen; Tanner, Rachel (Frontiers in Immunology, 2024)
First described by Wallis et al. in 2001 for the assessment of TB drugs, the direct mycobacterial growth inhibition assay (MGIA) offers a tractable ex vivo tool measuring the combined influences of host immunity, strain virulence and intervention effects. Over the past 13 years, we have led efforts to adapt the direct MGIA for the assessment of TB vaccines including optimisation, harmonisation and validation of BCG vaccine-induced responses as a benchmark, as well as assay transfer to institutes worldwide. The direct MGIA has since been applied across species for the evaluation of novel prophylactic and therapeutic TB vaccine candidates, the study of clinical cohorts including those with comorbidities, and to further understanding of potential immune correlates of protection from TB. We have performed a systematic review on the primary published literature describing the development and applications of the direct MGIA from 2001 to June 2023 in accordance with the PRISMA reporting guidelines. We provide a comprehensive update on progress of the assay since its conception and critically evaluate current findings and evidence supporting its utility, highlighting priorities for future directions. The direct MGIA provides a valuable tool for the early evaluation of TB drug and vaccine candidates, clinical cohorts, and immune mechanisms of mycobacterial control.